Revitalizing Financial Freedom to Achieve a Sustainable Economy Based on Maqashid al-Shariah in Hifz al-Mal - Ubaidillah Mansur; Dede Nurohman; Ahmad Muhtadi Anshor (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
Global economic instability and poor financial planning have created significant challenges in achieving financial freedom, particularly in Indonesia, where low financial literacy, limited access to financial services, and inadequate savings exacerbate the issue. Integrating maqÄá¹£id al-sharÄ«â€˜ah, especially á¸¥ifáº“ al-mÄl, offers an ethical and sustainable framework for addressing these challenges and achieving inclusive financial freedom. This qualitative study employs a case study approach, utilizing data from academic journals, reports from international organizations, interviews with Islamic economics experts, and supporting statistics. The findings reveal that Sharia principles in investment and wealth management enhance financial inclusion, stability, and public trust. The principle of á¸¥ifáº“ al-mÄl safeguards assets and promotes responsible financial practices aligned with ethical and social objectives. By incorporating maqÄá¹£id al-sharÄ«â€˜ah in financial planning, individuals and societies benefit from improved well-being and sustainable economic development. This study highlights the synergy between financial freedom and sustainability, emphasizing education, justice, and resource efficiency as core strategies. Policymakers and individuals are encouraged to adopt sharia-compliant financial practices for long-term prosperity. While offering valuable insights, the study acknowledges its limitations and calls for further research on the role of digital financial technology in enhancing financial inclusion under maqÄá¹£id principles.Keywords: Financial Freedom, MaqÄá¹£id al-SharÄ«â€˜ah, á¸¤ifáº“ al-MÄl, Sustainable Economy, Financial Inclusion